Identification of Cation Reaction and Separation of Group I Cations - Olena Silvia; Olivia Ghina Olia; Rahma Dika Aulia Nasution; Rani Sakila Nasution; Silvia Deswinta Maharani Damanik (Journal of Global Research Education, 2024)
Qualitative analysis is an analytical method used to detect the presence of a chemical element in a substance whose composition is unknown. Cations are ions with a positive charge. Qualitative analysis is one of the most effective ways to study chemistry and the elements and their ions in solution. Qualitative analysis can be done in two ways, namely the dry reaction and the wet reaction. The dry method is usually used for solids, while the wet method is used for liquids (solutions) which mostly use water as a solvent. The dry way only provides the necessary information and that information is short term. Meanwhile, the wet method can be used for macro, semi-micro and micro analysis so that there are many advantages, for example the reaction occurs quickly and is easy to work on. Changes that occur in the wet method are the occurrence of precipitate, discoloration of the solution, and the emergence of gas. In the qualitative analysis method we use several reagents including group reagents and specific reagents, these two reagents are carried out to determine the type of anion or cation in a solution. The class reagents used for the most common classification of cations are hydrochloric acid, hydrogen sulfide, ammonium sulfide, and ammonium carbonate. This classification is based on whether a cation reacts with these reagents by forming a precipitate or not. The group I cations form insoluble chlorides, but lead chloride is sparingly soluble in water, and therefore lead never precipitates completely when dilute hydrochloric acid is added to a sample of the remaining lead ions it precipitates quantitatively with H2S in a mutual acidic solution. As well as group II cations, nitrates from group I cations are very soluble among sulfates - sulfates, lead is practically insoluble, while silver sulfate falls more. Cation - Cation in group I consisting of Ag+, Hg+, and Pb2+.